2005
DOI: 10.1128/aac.49.4.1337-1339.2005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Pharmacodynamics of Meropenem in Patients with Ventilator-Associated Pneumonia following Administration by 3-Hour Infusion or Bolus Injection

Abstract: The time that concentrations in serum are above the MIC (T>MIC) is the pharmacokinetic/pharmacodynamic parameter correlating with the therapeutic efficacy of ␤-lactam antibiotics. The aim of this study was to demonstrate the T>MIC of meropenem when administered by a 3-h infusion compared with that when administered by bolus injection. The study was conducted with nine patients with ventilator-associated pneumonia. Each subject received meropenem in three regimens consecutively: (i) bolus injection of 1 g every… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
93
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(103 citation statements)
references
References 15 publications
7
93
0
3
Order By: Relevance
“…Higher exposures will be required for isolates with higher MICs. Prolonged infusion dosing regimens of up to 4 h (50 % of the dosing interval) have been used to treat bacterial infections (Fehér et al, 2014;Jaruratanasirikul et al, 2005). Our analysis indicated that a dosing regimen of 2 g q8 as 4 h infusion will result in target attainment rates of 100, 100, 100 and 71 % for VIM-producing isolates with MICs 2, 4, 8 and 16 mg l 21 , respectively.…”
mentioning
confidence: 74%
“…Higher exposures will be required for isolates with higher MICs. Prolonged infusion dosing regimens of up to 4 h (50 % of the dosing interval) have been used to treat bacterial infections (Fehér et al, 2014;Jaruratanasirikul et al, 2005). Our analysis indicated that a dosing regimen of 2 g q8 as 4 h infusion will result in target attainment rates of 100, 100, 100 and 71 % for VIM-producing isolates with MICs 2, 4, 8 and 16 mg l 21 , respectively.…”
mentioning
confidence: 74%
“…For example, previous studies have shown that extending the infusion duration of meropenem from 30 min to 3 h increases the probability of bactericidal target attainment. 20,27 Despite this, synergistic activity between meropenem and other antibiotic combinations was only observed in one out of three strains. Therapy, Pandrug-resistant Acinetobacter species T-P Lim et al There was no antibiotic combination that reliably demonstrated synergistic activity against all isolates, although rifampicin-polymyxin and tigecycline-rifampicin combinations were bactericidal and synergistic for two of the three isolates, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…For the purposes of our study, the maximum clinically achievable meropenem concentration of 64 mg ml À1 , which represented a free peak concentration arising from a 2 g, 3 h infusion, was simulated. 20 Rifampicin was tested at 2 mg ml À1 , which represented a free peak concentration arising from a 600 mg, daily oral dose to maximize the use of the drug. 21 The concentrations of polymyxin B and tigecycline were tested at 0.5Â MIC to yield attainable experimental end points.…”
Section: Time-kill Studiesmentioning
confidence: 99%
“…Fatores farmacocinéticos como o tempo de meia-vida, a estabilidade do medicamento, diluente ideal, temperatura do local onde será infundido e o tempo de infusão são extremamente importantes. No caso do Meropenem, este é um antimicrobiano de amplo espectro da classe dos Carbapenens, uma das diversas famílias de β-lactâmicos, possuindo tempo de meia vida curto e rápido clearance, administração tempo-dependente, com frequente administração para otimização do T >CIM e cuja administração intravenosa com soro fisiológico a 0,9 % ou glicose a 5% exibe um perfil de perda significante do medicamento, também influenciado pela temperatura do ambiente, especialmente em países de clima tropical e após 8 horas de infusão (KITZES-COHEN et al, 2002;PUNYO, 2005;LEE et al, 2010).…”
Section: Discussionunclassified